2009
DOI: 10.1016/j.hrthm.2008.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure enhances susceptibility to arrhythmogenic cardiac alternans

Abstract: Background-Although heart failure (HF) is closely associated with susceptibility to sudden cardiac death (SCD), the mechanisms linking contractile dysfunction to cardiac electrical instability are poorly understood. Cardiac alternans has also been closely associated with SCD, and has been linked to a mechanism for amplifying electrical heterogeneities in the heart. However, previous studies have focused on alternans in normal rather than failing myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 37 publications
11
94
1
Order By: Relevance
“…Rapid pacing at a CL of 150 ms decreased calcium transient amplitude in normal and HF preparations by 14% and 6%, respectively, compared with baseline pacing (CL ϭ 600 ms); however, this difference did not reach statistical significance. Rapid pacing also induced calcium transient amplitude alternans, similar to that reported previously in normal and HF canine wedge preparations (41).…”
Section: Resultssupporting
confidence: 87%
“…Rapid pacing at a CL of 150 ms decreased calcium transient amplitude in normal and HF preparations by 14% and 6%, respectively, compared with baseline pacing (CL ϭ 600 ms); however, this difference did not reach statistical significance. Rapid pacing also induced calcium transient amplitude alternans, similar to that reported previously in normal and HF canine wedge preparations (41).…”
Section: Resultssupporting
confidence: 87%
“…An interesting implication of these results is that RAN could be antiarrhythmic in the settings of ischemia and congestive heart failure where the vulnerability to calcium alternans is also increased (Kapur et al, 2009a;Wasserstrom et al, 2009;Wilson et al, 2009) and where enhanced late I Na has been demonstrated (Maltsev et al, 2001(Maltsev et al, , 2007Undrovinas et al, 2002Undrovinas et al, , 2006Valdivia et al, 2005), although a link between these two effects remains to be investigated. Finally, it is important to note that RAN also blocks human ether a-go-go-related gene channels and thus might induce some of its electrophysiological actions independently from the blockade of I Na,L .…”
Section: Ran Blocks Effects Of Late I Na On Cardiac Calcium Cycling 389mentioning
confidence: 96%
“…In HF, some ionic currents and Ca 2+ transport proteins are remodeled, resulting in a longer APD, lowered Ca 2+ transient, elevated [Na + ], and enhanced propensity to the occurrence of alternans (O'Rourke et al, 1999;Wilson et al, 2009). According to the experimental reports (Wilson et al, 2009), the CL needed to initiate alternans has increased from 240 to 500 ms for canine ventricular cells in HF. They attribute this increased propensity to the reduced expression of SERCA in HF.…”
Section: Heart Failure and Alternansmentioning
confidence: 99%
“…In addition to the usually observed prolonged APD, depressed Ca 2+ transient, and elevated Na + concentration, the heart rate threshold for the onset of APD alternans is observed to be significantly lowered in HF (Wilson et al, 2009). Nevertheless, the governing factors underlying the enhanced susceptibility to alternans in HF are less understood.…”
Section: Introductionmentioning
confidence: 99%